PO95 | Idiopathic thrombocytopenic purpura in tuberculosis (Bleeding, Thrombosis and Vascular Biology)
Tuberculosis (TB) is a contagious disease in both developing and developed countries. The incidence is increasing due to bacilli resistant to many drugs and the human immunodeficiency virus (HIV). Since 2012, India has the highest incidence of the disease at around 2.2 million cases, accounting for 26% of the global incidence according to World Health Organization statistics. A wide range of hematological manifestations is observed in TB, where thrombocytopenia is common in miliary TB and thrombocytosis in pulmonary TB. Immune thrombocytopenic purpura (ITP) is characterized by a low platelet count accompanied by the presence of autoantibodies. The association of immune thrombocytopenic purpura and tuberculosis is a rare condition. In the case presented, anti-tuberculosis therapy was effective for both tuberculosis and thrombocytopenia, suggesting a causal link between tuberculosis and immune thrombocytopenic purpura.